Risk group characteristics and viral transmission clusters in South-East Asian patients infected with human immunodeficiency virus-1 (HIV-1) circulating recombinant form (CRF) 01-AE and subtype B - Rebecca A. Oyomopito (2018)
© 2015, Kaohsiung Medical University. Published by Elsevier Taiwan LLC. All rights reserved. Human immunodeficiency virus (HIV)-1 epidemics in Asian countries are driven by varying exposures. The epidemiology of the regional pandemic has been changing with the spread of HIV-1 to lower-risk populations through sexual transmission. Common HIV-1 genotypes include subtype B and circulating recombinant form (CRF) 01-AE. Our objective was to use HIV-1 genotypic data to better quantify local epidemics. TASER-M is a multicenter prospective cohort of HIV-infected patients. Associations between HIV exposure, patient sex, country of sample origin and HIV-1 genotype were evaluated by multivariate logistic regression. Phylogenetic methods were used on genotypic data to investigate transmission relationships. A total of 1086 patients from Thailand, Hong Kong, Malaysia and the Philippines were included in analyses. Proportions of male patients within countries varied (Thailand: 55.6%, Hong Kong: 86.1%, Malaysia: 81.4%, Philippines: 93.8%; p < 0.001) as did HIV exposures (heterosexual contact: Thailand: 85.7%, Hong Kong, 46.2%, Malaysia: 47.8%, Philippines: 25.0%; p < 0.001). After adjustment, we found increased subtype B infection among men who have sex with men, relative to heterosexual-reported exposures (odds ratio = 2.4, p < 0.001). We further describe four transmission clusters of eight to 15 treatment naïve, predominantly symptomatic patients (two each for subtype B and CRF01-AE). Risk-group subpopulations differed with respect to the infecting HIV-1 genotype. Homosexual exposure patients had higher odds of being infected with subtype B. Where HIV-1 genotypes circulate within countries or patient risk-groups, local monitoring of genotype-specific transmissions may play a role in focusing public health prevention strategies. Phylogenetic evaluations provide complementary information for surveillance and monitoring of viruses with high mutation rates such as HIV-1 and Ebola.